Adventures in Raspberry Pi - Philbin, Carrie Anne (Adventures In., 2015)
Adventures in Raspberry Pi, 2nd edition includes 9 cool projects that show you how to set up and start developing on your Raspberry Pi. Updated for the release of the Rev 3 board, this second edition covers all the latest features and tells you everything you need to know. Written specifically for 11-15 year-olds, this book uses the wildly successful, Raspberry Pi to explain the fundamentals of computing. You'll have a blast learning basic programming and system administration skills, beginning with the very basics of how to plug in the board and turn it on. Each project includes an instructional video so you can jump right in and start going through the lessons on your own. This hands-on book gets you up and running fast, with fun projects that let you explore. Learn how to "talk to" your Raspberry PiCreate games and stories with ScratchProgram with Turtle Graphics and PythonCode music and create a Raspberry Pi jukeboxIf you want to get started programming today, Adventures in Raspberry Pi is the ultimate hands-on guide. The EPUB format of this title may not be compatible for use on all handheld devices